Maternal Diet Influences Association of Gestational Weight Gain and Birth Weight Among Undernourished Mothers - Raje, Swati; Rao, Shobha (European Journal of Applied Sciences, 2022)
Objective: Maternal nutrition intervention improves birth outcomes in undernourished but not in well-nourished populations. Therefore, objective was to examine its role in association of weight gain and pregnancy outcome in undernourished mothers. Design: Prospective study Setting: Obstetrics and Gynaecology out patients department of Rural Hospital Talegaon, Participants: Mothers (n=370) registering within 20 weeks of gestation were studied for socioeconomic variables, diet, anthropometric measurements and were followed up till delivery. Results: Mothers were undernourished with mean weight 45.9±7.3 kg, height150.8±6.1 cm and BMI 20.2±3.1kg/m2. In fact proportion of mothers below LBW risk cur off for weight (38Kg), height (<145 cm) and BMI(18.5 kg/m2 ) was respectively 9.8 %, 8.6 % and 32.8%. Mothers in lower tertile of weight (<42.5 Kg), BMI (<18.5Kg/m2) body fat (<21.8%) had babies with significantly lower birth weights with highest prevalence of LBW. Maternal BMI associated inversely with weight gain but positively with birth weight indicating that foetal growth was not benefitted fully by gained weight in undernourished mothers. Consumption of milk/milk products, fruits, non-vegetarian foods, dal and roti was associated with birth weight but not with weight gain. Comparison of mothers of LBW and normal weight babies within low (18.5 kg/m2) and high (≥21.1kg/m2) BMI groups showed that consumption of milk was discriminatory, indicating importance of proteins and micronutrients in facilitating foetal growth. Conclusion: Consumption of milk facilitated sparing of gained weight for foetal growth among undernourished mothers and promoting it could be a simple public health approach for prevention of LBW in rural India.